The impact of hand washing and correlation with anxiety during the COVID-19 pandemic period (Research, Society and Development, 2023)
Hand hygiene is one of the main measures regarding the prevention of transmission of various diseases, among which COVID-19 stands out. After all, it is known that its transmission occurs when the virus comes into contact with the mouth, nose or eyes, through unwashed hands. It is noted, therefore, that keeping your hands clean prevents infection and transmission of the disease. Taking this information into account, the present study discusses the impact of handwashing, correlating it with anxiety during the SARS-CoV-2 (COVID-19) pandemic. The investigation of the theme, the research problem presented here, arises from the need to understand the essential social links that will undoubtedly contribute not only to health professionals, but also to academics, teachers and the community in general. As for the methodological criteria, the research was developed using the exploratory-descriptive method, whose choice was fundamental in terms of data collection, as well as the treatment of the information obtained, that is, the analysis of the population and the investigated criteria, at which point that the research is directed to the examination of the data in an analytical and descriptive way. Finally, the present study aims to bring about the discussion, the identification of the main problems correlated with anxiety experienced by health professionals directly involved in coping with the COVID-19 pandemic, as well as pointing out future actions and strategies for the protection and prevention of anxiety disorders.